PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN NOTEBOOK ACER DI SURABAYA - SYAPUTRA, DHANDY (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
This studyaims to determine if the image of the brand Acer influence purchasing decisions laptop brand in HiTech Mall Surabaya. The focus of this studyis quantitative, and the type ofsurvey researchis to analyze the causal variables. Because in this study population is infinite, then on the basis of the theories mentioned above,this study used a sample with a total of 100 samples, of which divides the total sample of 100 samples in two groups, namely in the official sale Acer laptop shop and service centerin thehigh-tech business center Surabaya, calculated in proportion to the distribution of samples in each group, respectively 50 samples per group. Based on the result sof research and analysis and hypothesis testing of the findings of this study showed that brand image significantly influences the purchase decision. This means that if a brand image that is attached to a product (laptop Acerbrand) is good, then the decision to buy the product (brand notebookAcer) also increased or positive. Keyword :BrandImageand Purchase Decision